Structure of a VP1-VP3 complex suggests how birnaviruses package the VP1 polymerase. - Bahar, M; Sarin, L; Graham, S; Pang, J; Bamford, D; Stuart, D; Grimes, J (2013)
Infectious pancreatic necrosis virus (IPNV), a member of the family Birnaviridae, infects young salmon, with a severe impact on the commercial sea farming industry. Of the five mature proteins encoded by the IPNV genome, the multifunctional VP3 has an essential role in morphogenesis; interacting with the capsid protein VP2, the viral double-stranded RNA (dsRNA) genome and the RNA-dependent RNA polymerase VP1. Here we investigate one of these VP3 functions and present the crystal structure of the C-terminal 12 residues of VP3 bound to the VP1 polymerase. This interaction, visualized for the first time, reveals the precise molecular determinants used by VP3 to bind the polymerase. Competition binding studies confirm that this region of VP3 is necessary and sufficient for VP1 binding, while biochemical experiments show that VP3 attachment has no effect on polymerase activity. These results indicate how VP3 recruits the polymerase into birnavirus capsids during morphogenesis.